HUMOR AND SARCASM IN POLITICAL SPEECH DURING THE PRESIDENTIAL ELECTION IN THE USA - Azimova Marjona Salim qizi (PEDAGOGS, 2024)
Abstract. This article explores the role of humor and sarcasm in U.S. presidential election campaigns, examining their strategic use by candidates to connect with audiences, critique opponents, and navigate complex political landscapes. Through historical and contemporary case studies, the analysis highlights the benefits and risks associated with these rhetorical devices in shaping voter perceptions and influencing election outcomes.